Key financial and nonfinancial measures for performance evaluation of foreign subsidiaries - Azemina Mashovic (Journal of Contemporary Economic and Business Issues, 2018)
Foreign subsidiaries, as organization units of a multinational company, are profoundly involved in the value creation process for and within the company. The performance evaluation of foreign subsidiaries is a crucial issue for globally-active companies not only in regard to value creation for the company but also in stimulating international expansion, as well as in steering resource allocation. Therefore, within each particular foreign subsidiary, the multinational company should implement a well-organized performance evaluation system which will serve as an integrative and cognitive mechanism for organizing business operations in the host country. The established performance evaluation system should assess the foreign subsidiary's performance within the particular local environment, as well as within the multinational company as a whole. Thus, the optimization of resource allocation is most effectively achieved by the multinational company. The effective performance evaluation system includes both financial and nonfinancial measures. The aim of this paper is to provide an understanding of both key financial and nonfinancial measures that multinational companies use for performance evaluation of their foreign subsidiaries. The methodology applied consists of qualitative research techniques, such as analysis, comparative analysis, and synthesis. On the basis of the results obtained, the contribution of this paper is reflected in the determination of relevant financial and nonfinancial performance measures that multinational companies should use in order to evaluate the real performance of their foreign subsidiaries.
Keywords: F23; 330; balanced scorecard; financial measures; foreign subsidiaries; nonfinancial measures; performance evaluation